2019
DOI: 10.1002/mp.13884
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note: Film‐based measurement of gold nanoparticle dose enhancement for 192Ir

Abstract: Purpose-The purpose of this work is to introduce a simple yet accurate technique to measure the dose enhancement factor (DEF) of a citrate-capped gold nanoparticle (GNP) solution using EBT3 film in an 192 Ir setup.Methods-DEF is the ratio of absorbed dose in a solution compared to absorbed dose in water, assuming identical irradiation parameters. Citrate-capped GNPs were synthesized. An acrylic apparatus was constructed such that the EBT3 film was placed in charged particle equilibrium within the GNP solution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…A frequently cited GNP concentration is 7 mg/g, 4,7,27,28 which is well within the range of concentrations considered in this work. Further examples from MC studies include Bahreyni Toossi et al 29 who studied 10, 20, and 30 mg/g, Koger and Kirkby 20 who studied 5-30 mg/g, Brivio et al 21 who studied 10-66 mg/g, Bassiri et al 22 who studied 7, 18, and 50 mg/g, and Moradi et al 30 who studied 5-20 mg/g. For in vitro and in vivo studies, observed tumor gold concentrations also tend to vary, and depend strongly on GNP size, shape, any attached ligands, and more.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A frequently cited GNP concentration is 7 mg/g, 4,7,27,28 which is well within the range of concentrations considered in this work. Further examples from MC studies include Bahreyni Toossi et al 29 who studied 10, 20, and 30 mg/g, Koger and Kirkby 20 who studied 5-30 mg/g, Brivio et al 21 who studied 10-66 mg/g, Bassiri et al 22 who studied 7, 18, and 50 mg/g, and Moradi et al 30 who studied 5-20 mg/g. For in vitro and in vivo studies, observed tumor gold concentrations also tend to vary, and depend strongly on GNP size, shape, any attached ligands, and more.…”
Section: Discussionmentioning
confidence: 99%
“…who studied 10, 20, and 30 mg/g, Koger and Kirkby 20 who studied 5–30 mg/g, Brivio et al 21 . who studied 10–66 mg/g, Bassiri et al 22 . who studied 7, 18, and 50 mg/g, and Moradi et al 30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All experimental measurements were performed using an acrylic measurement apparatus developed in house at UT Health Mays Cancer Center as previously described in Bassiri et al (2019). The apparatus was designed to house an Ir-192 source placed inside a steel vaginal cylinder applicator.…”
Section: Experimental Set-up and Measurementsmentioning
confidence: 99%
“…Monte Carlo N-Particle code, version 6.2 (MCNP6.2, Los Alamos National Laboratory) was utilized to model the dose enhancement to a volume of GNPs placed below an Ir-192 seed. Experimental validation was performed using a previously-described dose measurement apparatus (Bassiri et al 2019) developed and built in-house. Herein we provide a full description of our MCNP6 model, including the source and nanoparticle-containing phantom and the important parameters used.…”
Section: Introductionmentioning
confidence: 99%